Morphometric analysis of orbit in Turkish population: a MDCT study - Ahmet Kağan Karabulut; Nadire Ünver Doğan; Mustafa Koplay; Büşra Pirinç; Zeliha Fazlıoğulları (Genel Tıp Dergisi)
Objective: The orbit is an important cavity containing vision-related formations and important neurovascular structures, and adjacent to various regions. This study aimed to evaluation, by multidedector computed tomography (MDCT) images, the morphometry of orbit by examining its changes according to gender and body side, and developments according to age, in Turkish population. Materials and Methods: A total of 200 individuals’s (94 females,106 males;400 sides) MDCT images were evaluated. Images were examined according to the gender, body side, and the anatomical structures development. Results: The height, width and depth of the orbit were determined as 36.04±2.97 mm, 32.33±2.59 mm, 38.35±3.32 mm on the right side, 35.79±3.18 mm, 32.29±2.67 mm, 38.13±3.21 mm on the left side, respectively, in healthy subjects. The height and width of the orbit were found to be statistically significantly larger on both sides in men than in women (p˂0.05). Conclusion: Comprehensive information about the orbit and associated apertures is quite important for clinicians working in this area, damage to these structures can cause serious complications. In addition, determining the morphometry of the orbit can be used as an important parameter for determining gender, age and race in forensic medicine.